2010
DOI: 10.1002/acr.20215
|View full text |Cite
|
Sign up to set email alerts
|

Riedel's Thyroiditis and Multifocal Fibrosclerosis are part of the IgG4‐related systemic disease spectrum

Abstract: Objective. Riedel's thyroiditis is a chronic fibrosing disorder of unknown etiology often associated with "multifocal fibrosclerosis." IgG4-related systemic disease is characterized by IgG4؉ plasma cell infiltration and fibrosis throughout many organs. We hypothesized that Riedel's thyroiditis is part of the IgG4-related systemic disease spectrum. Methods. We searched our institution's pathology database using the terms "Riedel's," "struma," "thyroid," and "fibro-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
182
1
14

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 300 publications
(206 citation statements)
references
References 33 publications
4
182
1
14
Order By: Relevance
“…27,30,31 As a result of the histological similarity, confusion has been noted in the literature regarding Riedel's thyroiditis and fibrous variant of Hashimoto's thyroiditis. 23 Most recently, an association between Riedel's thyroiditis and IgG4-related disease has been described by Dahlgren et al 32 They demonstrated excessive numbers of the IgG4-positive plasma cells in Riedel's thyroiditis samples. This observation would seem to further blur the distinction between the IgG4-related Hashimoto's thyroiditis and Riedel's thyroiditis.…”
Section: Discussionmentioning
confidence: 97%
“…27,30,31 As a result of the histological similarity, confusion has been noted in the literature regarding Riedel's thyroiditis and fibrous variant of Hashimoto's thyroiditis. 23 Most recently, an association between Riedel's thyroiditis and IgG4-related disease has been described by Dahlgren et al 32 They demonstrated excessive numbers of the IgG4-positive plasma cells in Riedel's thyroiditis samples. This observation would seem to further blur the distinction between the IgG4-related Hashimoto's thyroiditis and Riedel's thyroiditis.…”
Section: Discussionmentioning
confidence: 97%
“…Disparate disorders such as Mikulicz's syndrome, Kü ttner's tumor, multifocal fibrosclerosis, and eosinophilic angiocentric fibrosis are now considered to fall within this disease spectrum. 7,[17][18][19] Although their presenting symptoms are highly variable, the features that tie these disease conditions together are a common histological appearance, elevated serum and tissue levels of IgG4, and a response, generally swift, to immunosuppression.…”
Section: Introduction and Historical Perspectivementioning
confidence: 99%
“…Many different terms have been used to describe conditions that have become more recently recognized as members of a spectrum of clinical involvement in IgG4-related systemic disease (31,(35)(36)(37)(38). Full recognition of the disease is challenging, as involvement of different organs affected is often metachronous.…”
Section: Discussionmentioning
confidence: 99%